Analisa Hambatan, Stabilitas, dan Seakeeping Kapal Patroli Lepas Pantai - Alif Nur Rochmad; I Putu Shindu Asmara; Sumardiono Sumardiono; Benedicta Dian Alfanda (INOVTEK POLBENG, 2022)
Offshore Patrol Vessel (OPV)  are the result of technological development to defend the sea area. Fins Undership are fins-shaped devices located at the bottom of the ship's hull. The use of anti-roll systems (fins) on the ship is able to influence the rolling motion response on the ship. It is expected that when shooting conditions or avoid enemy attacks remain in a stable condition and in good performance. The addition of fin variations at the bottom of the ship's hull is a method used to change the resistance value and rolling moment arising from the ship's hull which is immersed in water. Calculation of ship resistance and rolling moment can be done through the Computational Fluid Dynamics (CFD) simulation method with the type of ship to be used is Offshore Patrol Vessel (OPV). Types of fins angle variation used are angles of 30°, 35°, 40° and 50°. So that it can be compared the resistance value and rolling moment with and without fins undership. The results of the study with the addition of Undership Fins on the underside of the hull influence the resistance and rolling moment of the ship. The results of simulation fins with NAIAD 525 type at a service speed of 22.4 knots, the angle of 30° has the lowest resistance value compared to other angles with a value at Maxsurf 945.3 kN and with Ansys CFD 933.708 kN. But the value of the engine power at an angle of 50° fins has the smallest value of 10.892,367 kW. As for the rolling moment value, the angle of 50° has the smallest rolling moment value with a value of 4.191.226.25 N.m at a frequency of 0.4 rad/s.